Effect of working medium on the noise and vibration characteristics of water hydraulic axial piston pump. (1st December 2021) - Pang, Hao; Wu, Defa; Deng, Yipan; Cheng, Qian; Liu, Yinshui
Abstract: Water hydraulic axial piston pump (WHAPP) is widely used in underwater vehicles. The noise and vibration of WHAPP are important for the concealment of underwater vehicles. In some hydraulic system, the oil and water inevitably permeate each other, resulting in changes of working medium characteristics and the vibration and noise of the WHAPP. In this study, the effect of working medium on the noise and vibration of WHAPP was researched through experimental and theory simulation methods. The noise and vibration are measured and compared when the WHAPP use different fluid (water or oil) as working medium. The results show that noise and vibration of WHAPP using oil as working medium are larger than that of using water as working medium, when the pressure is greater than 4 MPa. The simulation results show that the flow and pressure pulsation of oil is larger than that of water, which contributes to larger noise and vibration of oil. The differences of flow and pressure pulsation are mainly caused by the bulk modulus of working medium. This work also expresses that the effect of working medium characteristics must be considered for reducing the noise and vibration of axial piston pump.